PENGGUNAAN BAHASA DAERAH DENGAN MENGGUNAKAN MEDIA FILM TARUNG SARUNG OLEH ARCHIE HEKAGERY PADA SISWA SMA KELAS X DI SEKOLAH MA TARUNA TEKNIK AL JABBAR - Lubis, Ramadianti (Jurnal Bahastra, 2023)
Language as a tool for interaction between humans in society has a social nature. Regional languages contain the wisdom of a society, there are cultural values contained in regional languages. Regional language is also a reflection of a community in a certain area. Film is the product of culture and means of artistic expression. The purpose of this study is to determine the use of regional languages. The method used in this research is experiment, pre test and post test. Data collection techniques were carried out by watching films and understanding the data obtained, then determining the score for each variable, calculating the average value and standard deviation of the sample data. the results of this study concluded that there was an increase in the use of regional languages by using the film media tarung sarong.